Functional ecology of Nothofagus pumilio regeneration in relation to light availability - Martínez Pastur, Guillermo José (2006)
The silvicultural proposals for Nothofagus pumilio forests are mainly based on canopy open to stimulate regeneration growth by modifying water and light availability at understory level. Seedlings and saplings often survive as tolerant species and grow slowly for a long time (up to 20 years) under shaded overstory. However, when canopy is open by harvesting or wind-throws, young trees acting as intolerant species and can quickly colonize the opened areas. The objective was to make a comparative and functional approach analyzing morphological and physiological characteristics of N. pumilio seedlings, growing in a pre-defined light gradient under controlled conditions of irrigation and temperature. Seedlings of 2-3 years were collected in a closed canopy natural stand during September. Then, they were transferred to pots under a greenhouse, where three light levels were assayed (4%-26%-64% of the total natural incident light). Irrigation was made manually, maintaining a soil humidity of 40-60% soil capacity, while temperature was controlled through forced ventilation (less than 24°C). Thirty six plants in 6 clusters per each treatment where measured during January (height, number, size and shape of leaves, branch number and insertion angle), while 6 plants (one per cluster) was selected for physiological parameters measurement (dark respiration rate, light compensation point, photochemical efficiency, light saturation point and chlorophyll content). Photo-respiration was measured using an infra red gas analyzer of CO2 model S151 of Qubit System Inc. with a leaf chamber of 9 cm². Twenty-three variables related with three functional levels (leaf, shoot and crown, whole plant) were analyzed. At leaf level, most of physiological variables were higher in luminous treatment, while biometric variables were higher in middle light treatment. This last treatment has more chlorophyll a-b (0.033 and 0.011 mg/cm²), while luminous treatment has more carotenoids (0.010 mg/cm²). However, dark treatment presented the lower specific leaf mass (0.0007 g/cm²). At shoot and crown level, no differences were found in branch number and insertion angle, but plants growing in middle light treatment were taller than the others (17 cm compared to 12 cm). At whole plant level, best values were found in middle light treatment. However, the higher leaf area ratio was measured in dark treatment (389 cm²/gr). Nothofagus pumilio seedlings have morphological and physiological characteristics related to tolerant species, but could quickly change to those adapted to intolerant species when the light availability increases. It is necessary to make comparative and functional models to develop better silvicultural treatments which maximize the seedling potential during the installation and early growth phase.